The effect of alkylation degree in hyperbranched polyester on modified heavy oil fluidity. (15th June 2023) - Quan, Hongping; Zhang, Jian
Graphical abstract: Highlights: For heavy oil with high resin content, this experiment is the first time to synthesize a hyperbranched polyester as flow improvers by poly (propylene glycol), trimesic acid and nonanoic acid. A series of tests on flow improvers with different alkylation degrees conclude that the appropriate alkylation degree, rather than excess or less, is helpful to improve the performance. This work innovatively used a white-light interferometer to observe the profile of resins. Abstract: As flow improvers (FIs) for Xinjiang heavy oil with a high content of resins, a series of hyperbranched polyesters with varying degrees of alkylation (FI-1 to FI-7) were synthesized from poly (propylene glycol) (PPG) with trimesic acid (TA) and different dosages of nonanoic acid (NA). Here, the effect of alkylation degree in the flow improver on modified heavy oil fluidity was investigated. Firstly, the evaluation test indicated that the performance of FI-3 was optimal with an appropriate dosage of alkylation modifier, and a rate of viscosity reduction of 56.16%. Supportingly, the chemical structures of three flow improvers with different alkylation degree were compared by Fourier transform infrared spectroscopy (FTIR) and 1 H-nuclear magnetic resonance spectra ( 1 HMR). Importantly, the results of Ultraviolet visible spectrophotometer (UV–Vis) showed that FI-3 with an appropriate alkylation degree can better promote the solubility of resins in toluene. The results of simulating studies expounded that the interaction of FI-3 and resin clusters was more sufficient, which made the aggregation degree of resin clusters lower. The results of scanning electron microscope (SEM), white-light interferometer and X-ray diffraction spectra (XRD) revealed that flow improvers can significantly impact the structure of resins. Collectively, this study make known that this type of hyperbranched polyesters with alkylated branched chains can inhibit the aggregation of resins to modified heavy oil fluidity. An appropriate alkylation degree could improve the performance by strengthening the synergistic effect of polar groups and lipophilic alkyl chains. This work has important implications for comprehending the interaction between amphiphile and heavy oil, which could be exploitable for modified polymers used as flow improvers.